2018
DOI: 10.1242/jcs.219311
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic recruitment of TRF2 to DNA damage sites promotes non-sister chromatid homologous recombination repair

Abstract: TRF2 (TERF2) binds to telomeric repeats and is critical for telomere integrity. Evidence suggests that it also localizes to non-telomeric DNA damage sites. However, this recruitment appears to be precarious and functionally controversial. We find that TRF2 recruitment to damage sites occurs by a two-step mechanism: the initial rapid recruitment (phase I), and stable and prolonged association with damage sites ( phase II). Phase I is poly(ADPribose) polymerase (PARP)-dependent and requires the N-terminal basic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 60 publications
3
18
0
Order By: Relevance
“…For this purpose, immunocytochemistry assays were performed to investigate the co-localization of endogenous LAP1, TRF2 and γ-H2AX in HeLa cells' nuclei in a baseline state and upon a short-term bleomycin exposure (200 µg/mL for 30 min, followed by 6 h of recovery). A general analysis by confocal microscopy revealed that all proteins are located at the expected nuclear compartments irrespective of the experimental condition, wherein γ-H2AX ( Figures 6A and 7A) and TRF2 ( Figures 7A and 8A) are typically dispersed across the nucleoplasm whereas LAP1 is mostly distributed throughout the NE (Figures 6A and 8A), being consistent with previous descriptions for each protein [18,22,44,59,60]. Regarding their fluorescence intensity in the nucleus, the results indicated that, overall, the abundance of the three proteins augments after cell exposure to the DNA-damaging treatment comparatively to the control group (Supplementary Figure S4A,C,E), thus confirming the prior findings ( Figures 2C, 4B and 5B).…”
Section: Lap1 and Trf2 Co-localize At The Nuclear Membrane And Intransupporting
confidence: 89%
See 3 more Smart Citations
“…For this purpose, immunocytochemistry assays were performed to investigate the co-localization of endogenous LAP1, TRF2 and γ-H2AX in HeLa cells' nuclei in a baseline state and upon a short-term bleomycin exposure (200 µg/mL for 30 min, followed by 6 h of recovery). A general analysis by confocal microscopy revealed that all proteins are located at the expected nuclear compartments irrespective of the experimental condition, wherein γ-H2AX ( Figures 6A and 7A) and TRF2 ( Figures 7A and 8A) are typically dispersed across the nucleoplasm whereas LAP1 is mostly distributed throughout the NE (Figures 6A and 8A), being consistent with previous descriptions for each protein [18,22,44,59,60]. Regarding their fluorescence intensity in the nucleus, the results indicated that, overall, the abundance of the three proteins augments after cell exposure to the DNA-damaging treatment comparatively to the control group (Supplementary Figure S4A,C,E), thus confirming the prior findings ( Figures 2C, 4B and 5B).…”
Section: Lap1 and Trf2 Co-localize At The Nuclear Membrane And Intransupporting
confidence: 89%
“…After showing that a protein complex formed by LAP1 and TRF2 occurs in vitro, we investigated the establishment of this interaction in human cells. We hypothesized that it could be constitutively active in the cell or, instead, be triggered by a specific signaling event, more precisely by DDR activation, given the previously reported inhibitory [33][34][35][36][37][38][39] and stimulatory [40][41][42][43][44][45][46] roles of TRF2 as well as the recently suggested involvement of LAP1 [29] in this biological process. Before directly addressing this question, cellular models of DNA damage induction were developed; these consisted in exposing HeLa cells to different concentrations of H 2 O 2 -a reactive oxygen species (ROS)-or bleomycin-a radiomimetic anticancer drug-for distinct time periods.…”
Section: Lap1:trf2 Interaction Occurs In Response To Dna Damage and Imentioning
confidence: 99%
See 2 more Smart Citations
“…By binding to the viral TMR, TRF2 may play a similar role by shielding the end of the viral genome from DDR. Second, TRF2 has been shown to participate in HR [70,71]. We therefore surmise that the presence of TRF2 at viral DNA favors chromosomal integration by facilitating HR events between the host telomeres and viral telomeric sequences.…”
Section: Plos Pathogensmentioning
confidence: 90%